A study on co-operative tax planning and computation compared with other types of business / Mohamad Yusop Musa - Musa, Mohamad yusop (1987)
A large number of co-operative societies which are subjected to taxation are not aware of the provisions of the Malaysian Income Tax Act 1967 and types of taxes that are applicable to them. They should else know the action that they have to take in regard to determining whether assessment has been made correctly or not. My intension has been to make this study as readable as possible. This small publication is meant to bring to an average employee in a co-operative society the relevant of the provisions in the Income Tax Act 1967 to the business undertaken by the society. I hope the reader can share the same pleasure and enjoy reading the study as much as I had in developing it. I take great pleasure in expressing my gratitute to the following who had been instrumental in making the study the reality. I am indebted to Puan, Faridah Ahmad ITM Lecturer for a critical reading of the manuscript and many useful suggestions. My thanks to puan Faridah Hj. Omar, assistant director, Inland Revenue (HQ) for certain material and helpful comment and to puan Noorhayati Ismail, Administrative Officer Department of Inland Revenue (HQ) for valuable assistance and permission to use the Income tax library.